Would satisfaction with smart speakers transfer into loyalty towards the smart speaker provider? - ShinYoung Hwang (International Telecommunications Society (ITS), 2018)
Voice-enabled smart devices are poised to become the next new thing as it provides convenience in fulfilling users' instant needs. The ability to provide information, control home systems, and manage daily schedules has made smart speakers become the new gateway to users' personal spaces. The current smart speaker market however is dominated by IT or media firms instead of traditional audio manufacturers. By using its strong user base and existing array of services, smart speakers are perceived as a new opportunity to lock-in users to the service provider's platform. This study examines the extent to which consumer satisfaction with the smart speaker influences continuous usage intentions and most importantly, loyalty toward the smart speaker provider. Satisfaction is measured based on the system and information quality of the smart speaker. The empirical findings are drawn from 326 smart speaker users in Korea. The study finds that user satisfaction is an important asset that influences users' future intentions in using the smart speaker and remaining loyal to the service provider. As the smart speaker market becomes competitive, the race to lock-in users can be made through comprehensive approaches to developing the information and system quality of smart speakers.
Keywords: 330